Ultra elastic, stretchable, self-healing conductive hydrogels with tunable optical properties for highly sensitive soft electronic sensors. Issue 46 (17th November 2020) - Wu, Meng; Chen, Jingsi; Ma, Yuhao; Yan, Bin; Pan, Mingfei; Peng, Qiongyao; Wang, Wenda; Han, Linbo; Liu, Jifang; Zeng, Hongbo
Abstract : A self-healing hydrogel ionic conductor has been developed by combining dynamic covalent chemistry with nanofiller reinforcement and micelle crosslinking, and used for sensing of diverse human activities. Abstract : Conductive hydrogels are of great significance for soft electronic devices. However, the intrinsically weak nature, lack of fatigue resistance and self-healing capability, and the absence of stimuli-responsiveness of traditional conductive hydrogels hinder their application as durable, reliable and smart conductors to fulfill the increasing demands of modern electronics. Herein, we have developed a novel hydrogel ionic conductor by integrating nanofiller reinforcement with micelle cross-linking. The hydrogel was facilely prepared via one-pot polymerization of acrylamide and an amino-functionalized monomer in the presence of multiwall carbon nanotubes, aldehyde-modified F127 and LiCl. The dynamic chemical and physical interactions of the cross-linked network provide the hydrogel with a wide spectrum of properties, including excellent stretchability (1200%), skin-mimetic modulus, toughness, exceptional elasticity (recovery from 1000% strain), resistance to damage by sharp materials, self-healing properties (636% stretchability after self-healing) and high conductivity (3.96 S m −1 ). Besides, the rational design of the hydrogel endows it with multiple sensory capabilities toward temperature, strain and pressure. The hydrogel demonstrated cooling-induced whitening optical behavior. When exploited as a strain and pressure sensor to monitor diverse human motions, the prepared hydrogel sensor showed excellent sensitivity and reliability even for the acquisition of detailed waveform changes of radial artery pulses before and after exercise, suggesting its superior sensitivity compared to previously reported hydrogel sensors. The hydrogel was further integrated with an eye mask to monitor human sleep and showed high reliability for the detection of rapid eye movement (REM) sleep. This work provides new insights into the fabrication of multifunctional, smart and conductive materials, showing great promise for a broad range of applications like wearable sensors, artificial skins, and soft robotics.